I don’t have this huge backlog of good feeling for her: Role-relational trajectories in interview accounts of caring for a relative with dementia - Kruk, Bartłomiej (Yearbook of the Poznan Linguistic Meeting, 2020)
Caring for a family member with dementia involves multifaceted relational issues linked to the construction of caregiving as an emotional, symbolic and morally sanctionable practice inscribed in kin relations and dominant femininity (Paoletti 2007). As the disease disrupts taken-for-granted expectations for a person with dementia and the entire family, this qualitatively new situation necessitates the (re)negotiation of kin roles and responsibilities (Peel 2017; Purves 2011). By applying conversation analysis and membership categorization analysis to an audio-taped open-ended interview with an American female caregiver, this paper investigates in-depth how she discursively navigates complex familial role-relational trajectories while assisting her mother with dementia. The study examines the situatedness of role vis-á-vis self-other relations with assumptions about categories within the membership categorization devices ‘family’ and ‘gender’ being critical to this process. It documents how the participant contextualizes care experience not only in the standardized relational pair ‘daughter-mother’ but brings into focus a broader constellation of historical, contemporaneous or hypothetical aspects of kinship ties (e.g., with her parents, siblings or children), each of which invokes distinct expectations, responsibilities and loyalties which sometimes competing with other relations. The study thus exposes certain commonsense propositions concerning normative family role-relationships which function as powerful benchmarks for making life choices, interpreting one’s experiences, and morally evaluating oneself and others while providing care to kin with dementia.